Analisis Retribusi Pelayanan Parkir di Kota Jambi - Eka Warni; Firmansyah Firmansyah; Zulgani Zulgani (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
This research have purpose, 1 ) to know development acceptance for service parking area retribution in Jambi city and the contribution for retribution in region, PAD and acceptance region in Jambi city, 2) to know effectiveness degree acceptance for service Parking area retribution ini Jambi City about acceptance resources for 2006 until 2011 period,3) to know factors which is influence acceptance for service parking area retribution in Jambi city. Research method which is used for this research that is Analysis from primary data is got through dissemination quetiosn list and live interview with Skilled worker parking area in Jambi city.  For secondary data is time series during calculation era. Result of research to show that: 1) on the average during 2006 until 2011 period, the total of acceptance region in Jambi City has growing about 11,88%.  In the same period, PAD in Jambi City has growing about 18.44%, during 2006 until 2011 period, rapid of region retribution acceptance growing in Jambi City is About 4,45% and rapid of parking area retribution growing in Jambi City has increased about 13,62%. On the Average during 2006 until 2011 period contribution of parking area retribution to the total of acceptance region is about 0,29%.  In the same period contribution of parking area retribution to PAD in Jambi city is about 3,48% and contribution of parking area retribution to region retribution is about 11,44%. 2)  The efficiency coefficient of acceptance for parking area retribution in Jambi City can not be calculated because there is no cost of collecting for parking area retribution so the effeciency can not be calculated.  While the efficiency coefficient of acceptance for parking area retribution fo 2006 until 2011 period is very effective with value of mean contribution per year about 89,79%.  3) Among five factors which is influence acceptance for service parking area retribution, apparently, the most significant which is influence its increasing is value of parking area retribution while the othe factors do not influence for increasing and reduction of acceptance parking area retribution. Keywords: Retribution, contribution, effectiveness